Regional variation in healthcare utilization and mortality - Anna Godøy; Ingrid Huitfeldt (Statistics Norway, Research Department, 2018)
Geographic variation in healthcare utilization has raised concerns of possible inefficiencies in healthcare supply, as differences are often not reflected in health outcomes. Using comprehensive Norwegian microdata, we exploit cross-region migration to analyze regional variation in healthcare utilization. Our results indicate that hospital region factors account for half of the total variation, while the rest reflect variation in patient demand. We find no statistically significant association between the estimated hospital region effects and overall mortality rates. However, we document a negative association with relative utilization-intensive causes of death such as cancer, suggesting high-supply regions may achieve modestly improved health outcomes.
Keywords: H51; I1; I11; I13; 330; healthcare supply; healthcare demand; healthcare spending; regional variation; health outcomes